Taking time to act : a guide to cross-curricular drama - Ball, Chris, 1935- (Heinemann, 1995)
The teacher who wants to use drama in the classroom either for its own sake or as a tool in other areas of the curriculum will find Taking Time to Act an engaging book full of commonsense advice and inspiration. Authors Chris Ball and John Airs, drama specialists and teachers, look at the many common concerns teachers have and offer suggestions about setting aside a time and a place for drama; using drama to counter thoughtless and hateful stereotypes; and using drama to enhance not only literature but also math, science, social studies, and history. With photos of actual drama events and lively cartoons by Bill Stott, this book is a sound combination of theory and practice. Teachers with or without drama experience will find Taking Time to Act an invaluable addition to their reference library.